A Rare Case of Multiple Oblique Facial Clefts with Supernumerary Teeth: Case Report - Ramanathan, Manikandhan (Thieme Medical Publishers, 2012)
Oblique facial clefts are rare congenital anomalies that can present alone or in association with other craniofacial anomalies. A high degree of clefting in the embryo may lead to hyperdontia secondary to dichotomy of the dental lamina. Multiple facial clefts with hyperdontia are clinically challenging and demand comprehensive rehabilitation. This article reports a case of multiple oblique facial clefts of variable severity with multiple supernumerary teeth in a 12-year-old boy. The varied clinical presentation along with the rarity of the occurrence mandate documentation.